2018
DOI: 10.1111/ced.13679
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment with ustekinumab and vacuum-assisted closure therapy in recalcitrant myelodysplastic syndrome-associated pyoderma gangrenosum: case report and literature review

Abstract: Click https://www.wileyhealthlearning.com/ced.aspx for the corresponding questions to this CME article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 10 publications
(9 reference statements)
2
12
0
1
Order By: Relevance
“…The positive clinical response documented here is congruent with a growing number of cases also demonstrating improvements in recalcitrant PG with the use of ustekinumab. 57 Therefore, this case further supports the use of ustekinumab in therapy for PG and also draws attention to the probable contribution of IL-23 in disease pathogenesis.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The positive clinical response documented here is congruent with a growing number of cases also demonstrating improvements in recalcitrant PG with the use of ustekinumab. 57 Therefore, this case further supports the use of ustekinumab in therapy for PG and also draws attention to the probable contribution of IL-23 in disease pathogenesis.…”
Section: Discussionsupporting
confidence: 69%
“…4 Correspondingly, cases have emerged suggesting ustekinumab, a humanized monoclonal antibody targeting the shared p40 subunit of IL-12 and IL-23, may hold promise for inducing remission of refractory PG. 57 Here, we, adding to this body of literature, demonstrate the use of ustekinumab to treat PG that developed in a medically complex patient already receiving systemic immunosuppressive therapy.…”
Section: Introductionmentioning
confidence: 80%
“…When the disease is mild or the lesions are superficial, topical medications could be used as monotherapy 15 . Otherwise, oral GCSs (0.5‐1 mg/kg/day) remain the first‐line treatment in the majority of cases 9,16 . In our case series oral GCSs were very efficacious in various types of PG (pustular, vegetative, bullous, ulcerative).…”
Section: Discussionmentioning
confidence: 70%
“…New evidences showed that surgical approaches with NPWT and STSG are safe treatment options if performed under adequate immunosuppressive therapy 25 . NPWT associated with ustekinumab was shown to be successful in a PG‐associated myelodysplastic syndrome 16 …”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review published in 2015 including 823 cases of PG, HMs have been found to be associated with this condition in 12.5% of patients, following inflammatory bowel diseases ( n = 537; 65.2%) and polyarthritis ( n = 133; 16.1%) [ 66 ]. Haematological malignancies associated with PG, which are a major cause of death in this disease [ 41 , 67 ], are mainly represented by acute and chronic myeloid leukaemia [ 68 , 69 ], myelodysplastic syndrome [ 70 ], multiple myeloma [ 71 ], monoclonal gammopathy of undetermined significance [ 72 ] and lymphoma [ 73 ]. Although IgG isotype gammopathies are overall more frequent, most monoclonal gammopathies associated with PG are of the IgA isotype [ 47 , 74 ].…”
Section: Neutrophilic Dermatosesmentioning
confidence: 99%